2018
DOI: 10.1002/chem.201801829
|View full text |Cite
|
Sign up to set email alerts
|

Ion‐Exchangeable Microporous Polyoxometalate Compounds with Off‐Center Dopants Exhibiting Unconventional Luminescence

Abstract: The synthesis of luminescent polyoxometalates (POMs) typically relies on the assembly of POM ligands with rare earth or transition metals, placing significant constraints on the composition, structure, and hence the luminescence properties of the resultant systems. Herein, we show that the ion-exchange strategy can be used for the synthesis of novel POM-based luminescent materials. We demonstrate that introducing bismuth ions into an ion-exchangeable, microporous POM compound yields an unconventional system lu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 62 publications
0
7
0
Order By: Relevance
“…These changes can be rationalized considering simultaneous action of spin–orbit interaction and the crystal field of different symmetry on the ion. , To date the structural role and coordination environment of Bi + in solids have not been studied carefully. Recently, a quite complicated influence of the Bi + ion on the crystalline host structure was demonstrated: Bi + selectively occupied specific sites in the crystalline framework, causing a disordered displacement of the initial site . Even less is known about Bi + behavior in glasses.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These changes can be rationalized considering simultaneous action of spin–orbit interaction and the crystal field of different symmetry on the ion. , To date the structural role and coordination environment of Bi + in solids have not been studied carefully. Recently, a quite complicated influence of the Bi + ion on the crystalline host structure was demonstrated: Bi + selectively occupied specific sites in the crystalline framework, causing a disordered displacement of the initial site . Even less is known about Bi + behavior in glasses.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a quite complicated influence of the Bi + ion on the crystalline host structure was demonstrated: Bi + selectively occupied specific sites in the crystalline framework, causing a disordered displacement of the initial site. 28 Even less is known about Bi + behavior in glasses. Nevertheless, strong dependence of its optical properties on the local environment allows us to assume that structural disorder of the glass can explain relatively high inhomogeneous broadening of the Bi + optical center observed in the present study.…”
Section: ■ Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…75 to tune the coordination environment. (ii) POM-based ionic solids as cation-exchangers: the next target would be to explore cooperative effects of the selectively adsorbed cations and POMs,55 especially as optical materials, magnetic materials, solid catalysts, etc. (iii) Reduction-induced cation-uptake in POM-based ionic solids: while it is difficult for conventional porous compounds such as zeolites and MOFs to support the geometry change in the framework that often accompany the redox processes, POM-based solids show great potential for the multiple and reversible uptake/release of cations with electrons 6064,73.…”
Section: Discussionmentioning
confidence: 99%
“…5d). 54 Recently, Sun and co-workers showed that the cation-exchange of Cs + in the cesium hydrogen salt of silicododecatungstate with Bi (BiO + and BiOH 2+ ) having stereoactive 6s 2 lone pair as a dopant, leads to near-infrared photoluminescence in the important biological and telecommunication optical windows, due to the asymmetric coordination geometry of the Bi species in the microporous framework 55. This result offers a new strategy for the preparation of POM-based luminescent systems via cation-exchange.…”
Section: Polyoxometalate-based Ionic Solids As Cation-exchangersmentioning
confidence: 99%